Quantifying target-specific motion in anal cancer patients treated with intensity modulated radiotherapy (IMRT). Issue 1 (October 2016) - Durrant, Lisa; Robinson, Maxwell; Hawkins, Maria A.; Van den Heuvel, Frank; Muirhead, Rebecca
Abstract: Background and purpose: Intensity modulated radiotherapy requires all target areas to be treated by a single radiotherapy plan. In anal cancer, the pelvic nodes, inguinal nodes and primary tumour represent three different targets. We aim to calculate target-specific motion in anal cancer radiotherapy, when delivered using a single pelvic online auto-match. Materials and methods: Twenty consecutive patients treated using IMRT at a single institution were studied. CBCTs were retrospectively re-matched around the inguinal nodes and primary tumour. Match values were recorded relative to origin, defined as pelvic CBCT auto-match. Systematic and random errors were quantified to determine target-specific motion and suggested margins calculated using van Herk formulae. Results: The suggested margins to cover the independent motion of the inguinal and anal targets for LR, CC and AP set up around the inguinal nodes were 1.5 mm, 2.7 mm and 2.8 mm; and the primary tumour were, 4.6 mm, 8.9 mm and 5.2 mm respectively. Conclusions: Target-specific set up will likely result in reduced treatment volumes and as such reduced toxicity. This is the first time a relationship has been described between pelvic bones, inguinal nodes and primary tumour. The PLATO study will prospectively assess the toxicity and outcomes of this target-specific margins strategy.